A new brooding feather star of the genus Dorometra (Echinodermata: Crinoidea: Comatulida: Antedonidae) from the Ryukyu Islands, southwestern Japan - Obuchi, Masami; Kogo, Ichizo; Fujita, Yoshihisa (Zootaxa, 2009)
A new comatulid of the family Antedonidae, Dorometra sesokonis n. sp., is described from coral reefs of the Ryukyu Islands, southwestern Japan. The new species is extremely small with ten short arms and a unique pinnulation in which some proximal pinnules are absent or poorly developed in most specimens. Additionally, cirrals and brachials of D. sesokonis are elongated and partly colorless. The combination of these morphological characters makes the new species appear like juvenile specimens, regardless of sexual maturity. This species also has remarkable reproductive habits, exhibiting both external brooding and hermaphroditism.